SPIRAL CT A SEARCH ENGINE FOR DIAGNOSING MULTIPLE CANALS - A RARE CASE REPORT - Halkai, Kiran; Halkai, Rahul; Hegde, Mithra N.; S., Sapna; M., Narender Reddy (Journal of Health and Allied Sciences NU, 2014)
Successful treatment of any case mainly depends on proper diagnosis; this is particularly true when we are doing an endodontic treatment. Internal anatomy of root canal system varies a lot and predisposes to inadequate root canal preparation and should be recognized before or during treatment. Proper knowledge of these anatomical variations and proper diagnosis are of paramost important. As the routine diagnostic aids, radiograph is a two dimensional representation of a three dimensional object where the internal anatomy of the tooth cannot be appreciated properly. Spiral computed tomography (SCT) has got an advantage as it gives a 3 dimensional image of a given object. We present an interesting case of multiple canals in all the teeth except incisors in a single patient which was diagnosed with the aid of Dental CT and its potential role, this diagnostic method can help in the field of endodontics
Keywords: multiple canals; Spiral computed tomography